2014
DOI: 10.4103/0255-0857.136550
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic susceptibility pattern and genotyping of campylobacter species isolated from children suffering from gastroenteritis

Abstract: PCR assay method allows reliable detection of C. jejuni. C. jejuni was the most prevalent Campylobacter species. Gentamicin, amikacin and chloramphenicol were the most effective antibiotic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 46 publications
1
11
0
Order By: Relevance
“…Dallal identified a frequency of 0.9% for Campylobacter strains in acute diarrhea among children younger than 5 years of age in south Tehran (19). Various studies have reported Campylobacter frequencies, such as 3.0% in Senegal, 8.4% in Uruguay, 9.6% in Egypt, 9.7% in Tanzania, 9.3% in Uganda, 10.5% in Romania, 11.0% in Sudan, 12.7% in Ethiopia, and 22.6% in Ghana (11,12,15,(20)(21)(22)(23)(24)(25). Therefore, the average contribution of Campylobacter strains to AGE in children was about 9% in most studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dallal identified a frequency of 0.9% for Campylobacter strains in acute diarrhea among children younger than 5 years of age in south Tehran (19). Various studies have reported Campylobacter frequencies, such as 3.0% in Senegal, 8.4% in Uruguay, 9.6% in Egypt, 9.7% in Tanzania, 9.3% in Uganda, 10.5% in Romania, 11.0% in Sudan, 12.7% in Ethiopia, and 22.6% in Ghana (11,12,15,(20)(21)(22)(23)(24)(25). Therefore, the average contribution of Campylobacter strains to AGE in children was about 9% in most studies.…”
Section: Discussionmentioning
confidence: 99%
“…Campylobacter is one bacterial cause of AGE in developed countries (10). In developed countries, Campylobacter accounts for about 5% -20% of all cases of AGE in children younger than 5 years of age; in developing countries, this incidence ranges from 5% -35% (11,12). Campylobacter is transmitted through food and water and appears more often during the warm seasons (13) self-limiting in nature, antimicrobial therapy can reduce the severity of symptoms and shorten the course of the disease (14).…”
Section: Introductionmentioning
confidence: 99%
“…However, gentamicin, amikacin and chloramphenicol were the most effective antibiotics for the in vitro treatment of C. jejuni and C. coli isolates from Egyptian children suffering from gastroenteritis [11].…”
Section: Control and Prevention Interventionsmentioning
confidence: 97%
“…Later on, Campylobacter spp. were identified from patients with gastroenteritis in Cairo, Egypt using conventional and polymerase chain reaction (PCR) methods in 6.6% of human stool samples [10,11]. Recently, the epidemiology of Campylobacter among an Egyptian pediatric population was described and the results pointed out to the variability in Campylobacter spp.…”
Section: Epidemiologymentioning
confidence: 99%
“…Although campylobacteriosis is endemic in Egypt and considered a major cause for pediatric diarrhea [135], fluoroquinolone and macrolide resistance, was recently documented to increase in the isolated strains in Egypt [136][137][138][139][140][141][142][143][144][145][146][147]. In the period from 1991 to 2016, several studies screened and analyzed the resistance pattern of macrolides and FQ in campylobacters, especially C. jejuni and C. coli, in chickens and humans in several Governorates in Egypt as shown in Tables 2 and 3 [136][137][138][139][140][141][142][143][144][145][146][147]. Putnam [137] analyzed the annual prevalence of macrolides resistance rate in Cairo from 1995 till 2000, which was 0%.…”
Section: Incidence Of Resistance In Egyptmentioning
confidence: 99%